Contribution of the Achilles tendon to force potentiation in a stretch-shortening cycle - Fukutani, A.; Sawatsky, A.; Leonard, T.; Herzog, W. (The Journal of Experimental Biology, 2019)
Muscle force during concentric contractions is potentiated by a preceding eccentric contraction: a phenomenon known as the stretch-shortening cycle (SSC) effect. Tendon elongation is often considered to be the primary factor for this force potentiation. However, direct examination of the influence of tendon elongation on the SSC effect has not been made. The aim of this study was to evaluate the contribution of tendon elongation to the SSC effect by comparing the magnitude of the SSC effect in the rat soleus with and without the Achilles tendon. The rat soleus was subjected to concentric contractions without pre-activation (CON) and concentric contractions with an eccentric pre-activation (ECC). For the `with-tendon` condition, the calcaneus was rigidly fixed to a force transducer, while for the `without-tendon` condition, the soleus was fixed at the muscle-tendon junction. The SSC effect was calculated as the ratio of the mechanical work done during the concentric phase for the ECC and the CON conditions. Substantial and similar (P=0.167) SSC effects were identified for the with-tendon (318±86%) and the without-tendon conditions (271±70%). The contribution of tendon elongation to the SSC effect was negligible for the rat soleus. Other factors, such as pre-activation and residual force enhancement, may cause the large SSC effects and need to be evaluated.